2005
DOI: 10.1039/b500681c
|View full text |Cite
|
Sign up to set email alerts
|

Multi-walled carbon nanotubes for plasmid delivery into Escherichia coli cells

Abstract: Introduction of foreign genes into bacterial cells (transformation) is used for supplementing defective genes or providing additional biological functions. Transformation can be achieved using either chemical or physical methods, e.g., electroporation. Bulk electroporation offers several advantages over chemical methods, including high transformation efficiency, but its application is limited due to the high numbers of cells and plasmids needed as a result of the high death rate of cells during this process, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 11 publications
0
55
0
Order By: Relevance
“…Carbon nanotubes have been shown to have the potential to carry molecules and enter mammalian and bacterial cells (Pantarotto et al 2004b, Gao et al 2006. They could be beneficially used to deliver proteins (Hu et al 2004, Kam et al 2004, Pantarotto et al 2004a) genes and nucleic acids (Lu et al 2004, Rojas-Chapana et al 2005 and other biomolecules into cells. They can be functionalized with a variety of molecules for specific purposes.…”
Section: Introductionmentioning
confidence: 96%
“…Carbon nanotubes have been shown to have the potential to carry molecules and enter mammalian and bacterial cells (Pantarotto et al 2004b, Gao et al 2006. They could be beneficially used to deliver proteins (Hu et al 2004, Kam et al 2004, Pantarotto et al 2004a) genes and nucleic acids (Lu et al 2004, Rojas-Chapana et al 2005 and other biomolecules into cells. They can be functionalized with a variety of molecules for specific purposes.…”
Section: Introductionmentioning
confidence: 96%
“…CNTs were observed to bind to bacteria [20] and their high binding affinity to bacteria has been exploited to use them as bacterial filters [21]. In addition, the ability of CNTs to be spontaneously internalized by specific cells has recently stimulated numerous studies on transporting peptides, DNA, and RNA inside cells, both eukaryotic and prokaryotic, for tissue specific gene/drug delivery [12,[22][23][24][25][26][27][28][29][30]. Furthermore, owing to their absorbance of near-infrared (NIR) radiation [31] and relative transparency of most bio-tissues to NIR radiation [7][8][9][10][11][12][13], CNTs were suggested as promising agents for in vivo PT energy sensing and targeting of cancer cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Another study with Escherichia coli demonstrated that MWCNTs are able to form temporary "nanochannels" in the cell membrane, which lead to a decrease in cell viability (Rojas-Chapana et al, 2005). Given the antimicrobial effects of nanotubes, CNTs immobilized within the membrane skin might serve as a basis for inhibiting bacterial growth and reducing biofouling.…”
Section: Properties Of Carbon Nanutubes and Carboxylated Carbon Nanotmentioning
confidence: 99%